Oral administration of geraniol ameliorates acute experimental murine colitis by inhibiting pro-inflammatory cytokines and NF-κB signaling. Issue 9 (2nd September 2015) - Medicherla, Kanakaraju; Sahu, Bidya Dhar; Kuncha, Madhusudana; Kumar, Jerald Mahesh; Sudhakar, Godi; Sistla, Ramakrishna
<x xml:space="preserve">Abstract</x> Oral administration of geraniol ameliorates DSS-induced ulcerative colitis in mice.